2012
DOI: 10.1111/j.1365-246x.2012.05629.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the 2011-2012 submarine eruption off the coast of El Hierro (Canary Islands, Spain) from statistical analyses of earthquake activity

Abstract: SUMMARY The purpose of this work is to gain insights into the 2011–2012 eruption of El Hierro (Canary Islands) by mapping the evolution of the seismic b‐value. The El Hierro seismic sequence offers a rather unique opportunity to investigate the process of reawakening of an oceanic intraplate volcano after a long period of repose. The 2011–2012 eruption is a submarine volcanic event that took place about 2 km off of the southern coast of El Hierro. The eruption was accompanied by an intense seismic swarm and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 33 publications
4
66
0
4
Order By: Relevance
“…This time coincides to when López et al (2014) reports the beginning of the upward seismic hypocenter migration, the maximum release of seismic energy, and reaching the maximum strain rate of the preeruptive swarm and the first days of the eruption, and with gravity changes reported in Sainz-Maza Aparicio et al (2014). Ibáñez et al (2012) also observed a considerable decrease in b-values in that period compared to the previous weeks of the unrest.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This time coincides to when López et al (2014) reports the beginning of the upward seismic hypocenter migration, the maximum release of seismic energy, and reaching the maximum strain rate of the preeruptive swarm and the first days of the eruption, and with gravity changes reported in Sainz-Maza Aparicio et al (2014). Ibáñez et al (2012) also observed a considerable decrease in b-values in that period compared to the previous weeks of the unrest.…”
Section: Discussionsupporting
confidence: 72%
“…The 2011-2012 eruption was the first historical eruption in El Hierro and the first documented submarine eruption in the whole archipelago. The eruption was preceded by a three-month dense seismic swarm (Carracedo et al, 2012;Ibáñez et al, 2012;López et al, 2012;Martí et al, 2013). The anomalous activity started on 19 July 2011 beneath the center of the island, at a depth of ∼10-15 km (Domínguez Cerdeña et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This network is able to detect a seismic tremor with amplitude of the order of 0.1 cm 2 of reduced displacement. As suggested by McNutt (1992), this value can be obtained by taking into account the location of the eruption proposed in Pérez et al (2014) and the sensitivity of the seismic network, which is able to locate many earthquakes with magnitudes lower than 1 (see, for example, Ibáñez et al 2012 or the complete online IGN seismic catalog for the Canary I s l a n d s a t h t t p : / / w w w. i g n . e s / i g n / l a y o u t I n / (2010).…”
Section: Seismological and Geodetic Datamentioning
confidence: 99%
“…On 19 July 2011, an intense seismic swarm began at El Hierro Island Ibáñez et al, 2012;López et al, 2012;Martí et al, 2013b). Initial seismic activity of low magnitude (<M2.6) started in the central part of the island and migrated 3 km towards north at depths of 9-11 km over a period of one month (Domínguez Cerdeña et al, 2014).…”
Section: The 2011 Pre-eruptive Unrest At El Hierromentioning
confidence: 99%